(untitled) (Research, Society and Development, 2021)
Health has always been an essential issue for human beings to carry out from their daily tasks to the fulfillment of personal achievements such as desires, goals and dreams. After all, without health, none of this would be possible, through this it is understood that all people, without exception, have the right to do so. But there are still marginalized groups that have basic rights denied either directly or indirectly. Then comes the need to enunciate this theme so that it is possible to make a totally positive contribution to the readers affected by this review. The objective of the study is to discuss LGBTQIA+ health and identify points of improvement for providing comprehensive care to this group through the National Policy on Comprehensive Health for Lesbians, Gays, Bisexuals, Transsexuals and Transvestites (PNSILGBT) and other programs that cover these customers in particular. Addressing the fundamental contribution of nursing throughout the care process: primary, secondary and tertiary, which corresponds to Basic Health Units (UBSs), Emergency Care Units (UPAs), and hospitals, respectively. This is an integrative bibliographic review, carried out through research in electronic journals, books and legislation relevant to the subject.